GERAKAN NASIONAL PEMUDA BERKARAKTER DALAM PEMBANGUNAN MENTALITAS BUDAYA ANTI KORUPSI BERTINGKAT - Salisul khakim, Muhamad (Universitas Muhammadiyah Ponorogo, 2017)
The study was based on the background of the nation's problems are increasingly complex and fundamental, which is indicated by a weak cultural mentality that led to the character of the Indonesian nation in crisis, so the impact on the overall culture of corruption. This paper aims to discuss the development of anti-corruption culture mentality through national movement of youth character. Construction of this mentality is addressed to young people, because of the demographic bonus must be used to reconstruct the mindset of the character in accordance with the national identity. This movement is done through the education system that directly lead character on the basis of mental problems. This research method using descriptive qualitative approach. The data used is secondary data, namely the study of literature. Data analysis techniques in this study through three grooves of reduction, presentation, and verification of data. The results of this study is the relationship of weakness mentality of the Indonesian nation at the present time that need to improve fundamentally, as in the concept of an iceberg, namely the improvement of things that do not seem to fix the problems that appear to be systematically and comprehensively. The weakness can be overcome through character education, in an effort to establish an anti-corruption culture mentality.